The Influence of Content Marketing and Influencer Marketing on Consumer Purchase Interest in Mobile Iced Coffee Businesses in Dompu Regency. - Rupi Rahmiati; M Ikhwan Mansyuri; Sumarni Sumarni (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
This study aims to analyze the effect of Content Marketing and Influencer Marketing on Consumer Purchase Intention in mobile iced coffee businesses in Dompu Regency. This study used a quantitative method with a sample of 86 respondents who followed the Instagram account @kopling.dompu. Data were collected through questionnaires and analyzed using multiple linear regression with SPSS 23. The results showed that Content Marketing and Influencer Marketing had a positive and significant effect on Consumer Purchase Intention, both partially and simultaneously. The coefficient of determination (R²) value of 0.463 indicates that both independent variables were able to explain 46.3% of the effect on Consumer Purchase Intention, while the rest was influenced by other variables outside this study